Persistence of porcine reproductive and respiratory syndrome virus in intensive farrow-to-finish pig herds. - Chung, W B (1997)
An epidemiological study of porcine reproductive and respiratory syndrome (PRRS) within pig herds was conducted in 8 intensive farrow-to-finish pig farms. Persistence of PRRS virus (PRRSV) in pig herds was demonstrated by regular postmortem examination on 2 farms for a period of 2 y. Virus isolation and serum neutralization (SN) tests were performed on the sera collected from 9 groups of pigs (10 pigs/group) of various ages on 8 pig farms. Except for 1 farm, isolation rates of PRRSV reached the highest level of 70 to 100% of pigs 6 to 8 wk of age, which coincided with the lowest levels of maternal immunity. In 1 pig herd, sows (39 in total) with SN titers of < or = 1:2, 1:4-1:8, and > or = 1:16 were designated as groups 1, 2, and 3, respectively. Sera were obtained from their progeny (3 pigs randomly selected from each litter) at various ages from 0 to 22 weeks. A positive correlation (r = 0.377, P < 0.001) between the SN titers of sows and those of their progeny (1-week-old piglets) was observed. Pigs at the age of 6 wk, only 7.9% of group 1 pigs compared to 72.4% of group 3 pigs were seropositive. A significant difference (P < 0.01) in the percentage of pigs with PRRSV viremia among the 3 groups was observed, with the lowest level found in group 3 pigs. The isolation rates of PRRSV from serum reached the maximum at the age of 9 wk for all 3 groups. The results indicated that passively acquired serum antibodies conferred a protective effect for piglets; however, loss of passive immunity at various ages of pigs produced susceptible pigs that resulted in PRRSV persistence in the pig herds. Pigs 6 to 9 weeks old were the major reservoir for PRRSV in farrow-to-finish pig herds.